2018
DOI: 10.1007/s10508-018-1162-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Health Disparities Among Black Bisexual Men in the U.S.: Effects of Sexuality Nondisclosure and Gay Community Support

Abstract: Compared with Black gay men, Black bisexual men experience psychosocial health disparities, including depression, polydrug use, physical assault, and intimate partner violence (IPV). Black bisexual men are also less likely to disclose their sexuality, which may result in them receiving less sexual minority community support, exacerbating psychosocial health disparities. We assessed relationships between bisexual behavior, bisexual identity, sexuality nondisclosure, gay community support, and psychosocial morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…A great deal of cross-sectional and longitudinal research has found that internalized HIV stigma is one of the most important dimensions associated with adverse HIV outcomes such as ART non-adherence, higher viral load and poor mental health outcomes [ 56 , 64 ]. Other HIV-related stigma studies document the links between anticipated and experienced HIV stigma in health care settings [ 65 67 ], the mediating role of social isolation and depression among cisgender women [ 64 ], the role of sexuality nondisclosure and gay community support among Black bisexual men [ 68 ], and the mediating role of stress-contingent emotion regulation [ 69 , 70 ]. Dodge and colleagues are examining how state-level structural stigma impacts HIV prevention outcomes using national survey studies [ 71 ].…”
Section: Nih Icos With Hiv-related Stigma Research Approaches and Activitiesmentioning
confidence: 99%
“…A great deal of cross-sectional and longitudinal research has found that internalized HIV stigma is one of the most important dimensions associated with adverse HIV outcomes such as ART non-adherence, higher viral load and poor mental health outcomes [ 56 , 64 ]. Other HIV-related stigma studies document the links between anticipated and experienced HIV stigma in health care settings [ 65 67 ], the mediating role of social isolation and depression among cisgender women [ 64 ], the role of sexuality nondisclosure and gay community support among Black bisexual men [ 68 ], and the mediating role of stress-contingent emotion regulation [ 69 , 70 ]. Dodge and colleagues are examining how state-level structural stigma impacts HIV prevention outcomes using national survey studies [ 71 ].…”
Section: Nih Icos With Hiv-related Stigma Research Approaches and Activitiesmentioning
confidence: 99%
“…Negative attitudes toward bisexuality have a long history in both mainstream society and the larger lesbian/gay community (Mulick & Wright, 2002;Weiss, 2003;Welzer-Lang & Tomolillo, 2008;Yost & Thomas, 2012), manifested in stereotypes of bisexuals as confused, questioning, experimental, promiscuous, irresponsible, and unfaithful (Brewster & Moradi, 2010;Dyar & Feinstein, 2018). As a result, bisexual individuals often experience marginalization from both heterosexual and lesbian/gay communities, restricting their access to social support and validation (Friedman et al, 2019).…”
Section: The Most Controversial Group: Mostly-heterosexualsmentioning
confidence: 99%
“…Prior research has found that bisexually identified men may be less attached to gay communities (44,45) and therefore may experience less community support. Stigma experienced by bisexual Black men may influence not only the disclosure of their sexuality to friends, female sex partners and health care providers (46)(47)(48) but also their receptivity to prevention messages (49)(50)(51). Notably, among the seven bisexually identified men who complied with HMP, none reported female sex partners in the three months prior to their baseline interview, while 12 of the 29 bisexual non-compliers (41.4%) did report female sex partners.…”
Section: Discussionmentioning
confidence: 97%